2020
DOI: 10.3389/fpsyg.2020.00940
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Motor and Cognitive Inhibition for Hot and Cool Executive Functions: The Case of Quadrato Motor Training

Abstract: Enabling the ceasing of ongoing or prepotent responses and the controlling of interference, motor inhibition facilitates the development of executive functions (EFs) such as thought before action, decision-making, self-regulation of affect, motivation, and arousal. In the current paper, a characterization is offered of the relationship between motor inhibition and the executive functioning system, in the context of a proposed division into predominantly affective (hot) and cognitive (cool) components correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 99 publications
(115 reference statements)
0
28
0
Order By: Relevance
“…QMT requires a high level of attention divided between the body and the spatial coordinates incorporated in the quadrato space, as well as silent waiting for the next instruction. Previous studies showed that QMT enhances theta activity and improves cognition (for a recent review, see [163,164]). At the behavioral level, these changes have been associated with improvements in cognitive and psycho-emotional functioning [162,[165][166][167], considered important aspects of health and well-being.…”
Section: Quadrato Motor Training (Qmt)mentioning
confidence: 99%
“…QMT requires a high level of attention divided between the body and the spatial coordinates incorporated in the quadrato space, as well as silent waiting for the next instruction. Previous studies showed that QMT enhances theta activity and improves cognition (for a recent review, see [163,164]). At the behavioral level, these changes have been associated with improvements in cognitive and psycho-emotional functioning [162,[165][166][167], considered important aspects of health and well-being.…”
Section: Quadrato Motor Training (Qmt)mentioning
confidence: 99%
“…Thus a main feature of the QMT is inhibitory control needed to make a decision related to the instruction, as well as required in continuing to the following instruction rather than stopping when a misstep occurs [28]. This type of inhibitory control is directly related to the ability to regulate emotions through attention when, for instance, a mistake occurs or a distracting thought or inappropriate emotion arises, requiring "active waiting" [29].…”
Section: Ei In the Body: The Case Of Quadrato Motor Trainingmentioning
confidence: 99%
“…More specifically, by working with the minimal bodily self through paradigms like the QMT, which require us to be present in the current moment, we can enhance emotional regulation and in turn increase EI. The tasks required of QMT practitioners involve time perception and timing [63,64], emotional regulation [29], and the capacity to enhance self-determination through attention [65]. Keeping in mind that the central point in the sphere is thought to represent an equilibrium state in which attention is divided between extrinsic and intrinsic stimuli [45], it is notable that QMT requires intentional division of attention between the internal object -the body -and external surroundings, as well as sustained attention; together, these might lead to enhanced self-awareness, in which the somatic focus is mediated by alpha modulation.…”
Section: Qmt Smc Attention and Self-awarenessmentioning
confidence: 99%
“…While meditation has been generally categorized into these two types (in which focused attention meditation requires voluntary focusing of attention on a chosen object, and open monitoring meditation involves non-reactive monitoring of the content of experience from moment to moment), most meditative techniques lie somewhere on a continuum between the poles of these two methods [ 55 ]. For example, QMT includes both aspects, requiring both divided attention between body and external verbal commands, in parallel to waiting to the next command [ 56 ].…”
Section: Introductionmentioning
confidence: 99%